2019
DOI: 10.3390/ma12040587
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Deposition Temperature on the Phase Evolution of HfNbTiVZr High-Entropy Thin Films

Abstract: In this study, we show that the phase formation of HfNbTiVZr high-entropy thin films is strongly influenced by the substrate temperature. Films deposited at room temperature exhibit an amorphous microstructure and are 6.5 GPa hard. With increasing substrate temperature (room temperature to 275 °C), a transition from an amorphous to a single-phased body-centred cubic (bcc) solid solution occurs, resulting in a hardness increase to 7.9 GPa. A higher deposition temperature (450 °C) leads to the formation of C14 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 38 publications
4
36
1
Order By: Relevance
“…The non-relaxed multi-component alloy with an (undistorted) bcc structure has a lattice constant of 3.40 Å, whereas the supercell relaxation yielded a slightly smaller lattice constant of 3.36 Å. Previous theoretical calculations on the ideal (undistorted) alloy have reported a 3.40 Å lattice constant,36 in excellent agreement with our calculations, whereas previous experimental results have reported values in the range of 3.37 -3.46 Å 20,21,[36][37][38]. The values are plotted in Figure1together with data for the pure elements.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…The non-relaxed multi-component alloy with an (undistorted) bcc structure has a lattice constant of 3.40 Å, whereas the supercell relaxation yielded a slightly smaller lattice constant of 3.36 Å. Previous theoretical calculations on the ideal (undistorted) alloy have reported a 3.40 Å lattice constant,36 in excellent agreement with our calculations, whereas previous experimental results have reported values in the range of 3.37 -3.46 Å 20,21,[36][37][38]. The values are plotted in Figure1together with data for the pure elements.…”
supporting
confidence: 87%
“…To verify the theoretical modelling results, a multi-component alloy sample deposited within the framework of a previous study 21 was studied further, together with elemental references. XPS analysis showed that the coating had a near equimolar composition: Hf 22 Nb 19 Ti 18 V 19 Zr 21 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The process of phase separation during film growth was observed by F. Fritze et. all during deposition of HfNbTiVZr thin films [30]. The Authors observed growth of different phases on different substrate temperatures without annealing, but the substrate temperature was much lower than the temperature of phase separation for bulk samples.…”
Section: Discussionmentioning
confidence: 95%
“…A nanocomposite structure, which was composed of nanocrystalline grains embedded in an amorphous matrix, was formed, leading to an increase in hardness beyond the Hall–Petch breakdown. Fritze et al discovered that increasing the substrate temperature could promote phase transition in HfNbTiVZr HEAs 147. The HEAs, transforming from amorphous phase to BCC phase, then to BCC/Laves phase during this process, exhibited different hardness values, which showed the composite effect of phase structure.…”
Section: Property Adjusting Of Phase Engineered Heasmentioning
confidence: 99%